Regulation of GSK-3 Activity as A Shared Mechanism in Psychiatric Disorders - ARICIOĞLU, FEYZA (KURE ILETISIM GRUBU A S, 2014)
Glycogen synthase kinase-3 (GSK-3), a member of the serine/threonine kinase family was first identified as an inhibitor of the metabolic enzyme glycogen synthase and is now accepted as a widely influential enzyme responsible for many intracellular regulatory mechanisms with over 50 known substrates characterized. There are two mammalian GSK-3 isoforms encoded by separate genes: GSK-3 alpha and GSK-3 beta with high structural homology. Both GSK-3 alpha and GSK-3 beta are widely expressed in many tissues with the highest levels in the brain and their functions are generally considered to be indistinguishable. Unlike many other protein kinases, GSK-3 is constitutively dephosphorylated and active in resting cells. Phosphorylation of GSK-3 by other protein kinases such as PKA (Protein kinase A), AKT (Protein kinase B) and PKC (Protein kinase C) inhibits its activity. Today a growing body of evidence strongly suggests that increased GSK-3 activity is involved in the development of schizophrenia and mood disorders such as bipolar disorder, major depression and hyperactivity associated disorders. Thus, inhibition of overactive GSK-3 has become a promising target in the treatment of these psychiatric disorders. Herein we will briefly discuss the underlying mechanisms related to how GSK-3 is thought to participate in such diseases and will give examples of clinically important treatments that have a role in GSK-3 regulation.
Keywords: GSK-3; depression; bipolar disorder; schizophrenia; GLYCOGEN-SYNTHASE KINASE-3; NEUROTROPHIC FACTOR; PROTEIN-KINASE; ANTIPSYCHOTIC-DRUGS; SERUM-LEVELS; DIFFERENTIAL REGULATION; TREATMENT INCREASES; BETA-CATENIN; MOUSE-BRAIN; IN-VIVO